Perancangan Buku Cerita Pop-Up Petualangan Lentera Kunang-Kunang - Elizabeth Jessica Sentani (ULTIMART Jurnal Komunikasi Visual, 2015)
This research enables the design of a pop-up storybook about cooperating while learning and about social skills. This pop-up storybook is made to remind the importance of cooperation for children age 4-6. The research is made because of the decline in cooperation among children which is the result of lack of social interaction, development in technology, and parenting issues. The research covers data collected about children age 4-6, interviews with child psychologists, literature study, dan direct observation. Data results were then processed to build story, visual, and paper engineering techniques. Keywords: storybook, pop-up, social skills, cooperation, children